Defluoridation of groundwater using natural adsorbent - Singh N.L.; Singh N.; Kumar S.; Mishra P.K. (My University, 2025)
Fluoride is the major inorganic pollutant of natural origin found in groundwater. The safe limit of fluoride in drinking water is 1.0 mg/L (WHO). Several adsorbent materials have been tried in the past to find out an efficient and economical defluoridating agent. The most commonly used adsorbents are activated alumina and activated carbon. In present work, an effort has been made to remove the fluoride from groundwater by adsorption process. Rice-husk, saw-dust, naphtha ash have been used and adsorption has been studied by varying different parameters. Feasibility of adsorption at groundwater pH has been studied. It was found that among the three, Naphtha-ash acted as a good absorbent. Saw dust and rice husk also worked as good absorbents but saw dust requires contact time of 20 hrs for efficient adsorption while rice husk showed efficiency of 85-90% in contact period of 6hrs only. As Naptha ash is not available easily, and saw dust require a long contact period, rice husk, abundantly available in the region, can be used as a good adsorbent for removal of fluoride from groundwater. Copyright © EM International.